Large, isolated, congenital aneurysm of the anterior descending coronary artery. Issue 3 (September 1993) - Chen, Y T; Hwang, C L; Kan, M N
Abstract : A large congenital aneurysm, arising from the first diagonal branch of the left anterior descending artery in a 52 year old woman was diagnosed by transoesophageal echocardiography, computed tomography, and magnetic resonance imaging. Surgical closure of the aneurysm was successful.